Private Twilight: Wither Private Universities in Kenya - Munene, Ishmael I. (International Higher Education, 2015)
It is a trying time for private universities in Kenya. Declining market share and attendant financial woes are ominous signs for the once vibrant sector. The article identifies the blurring of institutional distinctiveness, government policy promoting public growth and public sector resurgence through the privatization as factors precipitating the private decline.